GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN KINERJA PERAWAT DI INSTALASI GAWAT DARURAT DI RUMAH SAKIT PADA MASA PANDEMI COVID-19 TAHUN 2022 - Christina Lombogia; Oksfriani Jufri Sumampouw; Junita Maja Pertiwi (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Introduction: Health services during the Corona Virus Disease (Covid-19) pandemic will be very different from the situation before Covid-19, because Hospitals must prepare stricter security procedures where PPI protocols are followed according to standards. Patient admission procedures will certainly experience the impact of changes including the universal use of masks, stricter screening procedures, abolishing visiting hours, and restrictions on patient companions and even separation of services for Covid-19 and non-Covid-19 patients. This affects the performance of hospital employees, especially in the Emergency Room (ER). Employee performance is influenced by many factors such as leadership style and work environment. The purpose of this study was to analyze the correlation between leadership style and work environment with the performance of emergency room nurses at the hospital during the Covid-19 pandemic in 2022. Methods: This is an observational study with a cross-sectional approach. This research was conducted in the Emergency Room of Hospital Prof. dr. R.D. Kandou Manado in March-May 2022. The respondents to this study were 118 nurses. The variables in this study are leadership style, work environment and performance. The instrument used is a questionnaire that has been validated by researchers. Data analysis carried out in this study was bivariate analysis using the Chi-Square test. Results: The results showed that the dominant respondents are distributed in female gender (75.4%), aged 36 years and under (59.3%), educated Bachelor/S1 (64.4%) and work 0-10 years (55.9%). Furthermore, it was explained that the respondents were mostly distributed in both categories for performance variables (66.9%), work discipline (73.7%), motivation (61.0%) and leadership style (57.6%) while the respondents' work environment variables distributed 50% each for good and bad categories. The results of statistical analysis showed that there was a correlation between leadership style (p=0.000) and work environment (p=0.002) with the performance of the nurses in the IGD RSUP Prof. dr. R.D. Kandou. Conclusion: it can be concluded that the leadership style and work environment are correlated to the performance of nurses in the Hospital so efforts are needed to improve leadership style and work environment to be excellent so that nurse performance becomes positive or increases.